(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
In order to study the hypercalcified sponges in reefal deposits of the Nayband Formation in Lut Block, the Garm Ab section near the village of Mehran Kushk, located about 20 km northeast of Ferdows city, was sampled. Eight horizons of reefal limestone beds are exposed in this section. The most important reef builders are hypercalcified sponges with some representatives of hexactinellids, scleractinian corals and other reef organisms. The field and lab-observations on rock units, sedimentary facies and faunal assemblages indicate the middle Norian-Rhaetian as the age of the reef horizons. Twenty-three sponge taxa, including 15 of the chambered sphinctozoans, 2 of hexactinellids sponges and 8 non-chambered inozoan were identified. The majority of recognized sponges are reported from the Nayband Formation from the other localities in central Iran. One new species identified as Cryptocoelia maxima n. sp. was recovered and is described here.